2013
DOI: 10.1016/j.aap.2013.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Safety climate dimensions as predictors for risk behavior

Abstract: This study examines the interactive relationship between three dimensions of safety climate (management commitment to safety, priority of safety, and pressure for production), and their impact on risk behavior reported by employees. The sample consisted of 623 employees from a chemical manufacturing organization in South Africa. Hierarchical regression analyses were carried out to test the direct effects and the interaction effect of the three safety climate dimensions on risk behavior. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 64 publications
(73 reference statements)
6
51
0
6
Order By: Relevance
“…productivity or efficiency) in their impact on safety performance. In this sense, Bosak et al (2013) showed that ''employees' risk behavior was negatively related to management commitment to safety and priority of safety and positively related to pressure for production'' (p. 256). In the same vein, Vinodkumar and Bhasi (2010) found that management commitment and safety rules and procedures predicted safety compliance directly whereas safety training and safety communication and feedback predicted safety compliance indirectly.…”
Section: Perceived Risk and Safetymentioning
confidence: 99%
“…productivity or efficiency) in their impact on safety performance. In this sense, Bosak et al (2013) showed that ''employees' risk behavior was negatively related to management commitment to safety and priority of safety and positively related to pressure for production'' (p. 256). In the same vein, Vinodkumar and Bhasi (2010) found that management commitment and safety rules and procedures predicted safety compliance directly whereas safety training and safety communication and feedback predicted safety compliance indirectly.…”
Section: Perceived Risk and Safetymentioning
confidence: 99%
“…22 Although safety climate was originally studied as a predictor of behavior and injury in the manufacturing sector, it has since been examined in other industries including retail, health care, petrochemical and chemical, laboratories, food, transportation, and packing plants. 8,21,[23][24][25][26][27][28][29][30][31][32][33] It has been extensively applied in the construction sector and we build upon our predecessors' work in this area. 18,[34][35][36][37][38] Using the safety climate construct as a theoretical framework, we investigated perceptions of workrelated hazards and potential work organization and safety factors among Hispanic construction workers in Lawrence, Massachusetts.…”
Section: Introductionmentioning
confidence: 99%
“…Organizations with vigorous safety climate have low injury rate because of effective safety climate and management commitment to safety (10). A study done in a chemical industry in South Africa showed the importance of management commitment to safety (11). Most existing researches confirm the association between safety climate and leadership.…”
Section: Introductionmentioning
confidence: 96%